2000
DOI: 10.1038/sj.gene.6363673
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 (chemokine receptor-5) DNA-polymorphism influences the severity of rheumatoid arthritis

Abstract: Chemokines are critical for the inflammatory process in autoimmune diseases such as rheumatoid arthritis (RA). The chemokine receptor-5 (CCR5) mediates chemotaxis by CC-chemokines and is expressed by lymphocytes with the Th1 phenotype and monocyte/macrophages. A 32 bp deletion in the CCR5 (CCR5-⌬32 allele) abolishes receptor expression in homozygotes, while CCR5-⌬32 carriers would express less receptor than wild-type homozygotes. This polymorphism is related to the resistance to HIV-1 infection and progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
2
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 11 publications
2
71
2
1
Order By: Relevance
“…Refined analysis by rheumatoid factor status and gender were precluded by the lack of availability of such information from all studies. Of the 5 studies, three studies provided proportion of female patients, 12,14,15 which ranged from 71 to 84%, similar to frequencies of female RA patients in other published studies. Only one study provided the proportion of patients positive for rheumatoid factor.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Refined analysis by rheumatoid factor status and gender were precluded by the lack of availability of such information from all studies. Of the 5 studies, three studies provided proportion of female patients, 12,14,15 which ranged from 71 to 84%, similar to frequencies of female RA patients in other published studies. Only one study provided the proportion of patients positive for rheumatoid factor.…”
Section: Resultsmentioning
confidence: 65%
“…It has been reported that individuals heterozygous for CCR5-D32 have a milder phenotype of disease. 12,15 However, others have concluded that the presence of CCR5-D32 does not influence the phenotype of RA. 13,17 Counter to the proposed role of CCR5 in RA are observations of individual RA patients who are homozygous for CCR5-D32.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a prelude to chemokine targeting in humans, one study has shown decreased severity and incidence of RA in patients with the CCR5 ⌬32 allele, which codes for a nonfunctional CCR5 allele (123,124). Another study showed that this allele was found less frequently in patients with RA (125).…”
Section: Chemokine Targeting Strategies In Human Ramentioning
confidence: 99%
“…The CCR5Δ32 is a genetic marker related to the severity of RA 115 . Recent study provides further evidence for a protective effect of the CCR5Δ32 variant on rheumatoid arthritis in a New Zealand cohort 116 .…”
Section: Rheumatoid Arthritis (Ra) and Related Diseasesmentioning
confidence: 99%